CLINIC AND COURSE OF EPILEPSY IN PATIENTS WITH COVID-19. (World Bulletin of Public Health, 2023)
The direct effect on the nervous system of previously known viral infections was evident. But the difference in the appearance of the disease and the changing clinical symptoms of the coronavirus have sharpened the knowledge of medical personnel and led to the foundation of new research. The Covid-19 infection caused a global pandemic and entered medicine in a new way.